Data mining for fuzzy diagnosis systems in LTE networks. Issue 21 (30th November 2015) - Khatib, Emil J.; Barco, Raquel; Gómez-Andrades, Ana; Muñoz, Pablo; Serrano, Inmaculada
Highlights: A Knowledge Acquisition learning algorithm is proposed for troubleshooting in LTE. A sensitivity analysis is performed on the proposed algorithm. The algorithm is tested with a live network scenario. The performance has been compared with a Bayesian Network based algorithm. Abstract: The recent developments in cellular networks, along with the increase in services, users and the demand of high quality have raised the Operational Expenditure (OPEX). Self-Organizing Networks (SON) are the solution to reduce these costs. Within SON, self-healing is the functionality that aims to automatically solve problems in the radio access network, at the same time reducing the downtime and the impact on the user experience. Self-healing comprises four main functions: fault detection, root cause analysis, fault compensation and recovery. To perform the root cause analysis (also known as diagnosis), Knowledge-Based Systems (KBS) are commonly used, such as fuzzy logic. In this paper, a novel method for extracting the Knowledge Base for a KBS from solved troubleshooting cases is proposed. This method is based on data mining techniques as opposed to the manual techniques currently used. The data mining problem of extracting knowledge out of LTE troubleshooting information can be considered a Big Data problem. Therefore, the proposed method has been designed so it can be easily scaled up to process a large volume of data with relatively low resources, as opposed to other existing algorithms. Tests show the feasibility and good results obtained by the diagnosis system created by the proposed methodology in LTE networks.